2022
DOI: 10.3389/fphar.2022.833077
|View full text |Cite
|
Sign up to set email alerts
|

Albuca Bracteata Polysaccharides Attenuate AOM/DSS Induced Colon Tumorigenesis via Regulating Oxidative Stress, Inflammation and Gut Microbiota in Mice

Abstract: Inflammation is an important risk factor in the development of inflammatory bowel disease (IBD) and colitis-associated colorectal cancer (CAC). Accumulating evidence indicates that some phytochemicals have anti-cancer properties. Polysaccharides extracted from Albuca bracteata (AB) have been reported to possess anti-neoplastic activities on colorectal cancer (CRC) models. However, it is still unclear whether they exert therapeutic effects on colorectal cancer. In this study, we investigate the properties of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…Accumulating evidence has highlighted that inhibition of inflammation and oxidative stress contributed to the control of AOM/DSS-induced CAC [ 59 ]. In this study, we found that WMP attenuated the AOM/DSS-induced CAC mainly by suppressing of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has highlighted that inhibition of inflammation and oxidative stress contributed to the control of AOM/DSS-induced CAC [ 59 ]. In this study, we found that WMP attenuated the AOM/DSS-induced CAC mainly by suppressing of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a decrease in the Ruminococcaceae family, Oscillospira and Lachnospira genus, species that are related to inflammatory processes [ 21 , 22 , 37 , 57 , 58 , 59 ], was also observed at the finasteride withdrawal [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether finasteride treatment may affect steroid levels in the male colon is still unknown. Additionally, the change in the gut microbiota composition previously observed [ 8 ] seems to suggest an inflammatory microenvironment with putative consequences on gut physiology [ 21 , 22 ]. In this context, it is also important to highlight that serotonin, which plays a crucial role in the regulation of several physiological functions, such as motility, secretion and visceral sensitivity [ 23 ], is also related to inflammatory responses in the gut [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The polysaccharides extracted from Albuca bracteata (ABPs) were homogeneous polysaccharides with glucose and mannose as the main monosaccharides. ABP treatment could increase the beneficial bacteria in the intestine (for example, g_ Oscillospira ) and total fecal short-chain fatty acid (SCFA) levels in colorectal cancer (CRC) mice . SCFAs are the main end products produced by the fermentation of dietary fiber in the intestines by the intestinal flora .…”
Section: Polysaccharides and Cancersmentioning
confidence: 99%
“…ABP treatment could increase the beneficial bacteria in the intestine (for example, g_Oscillospira) and total fecal short-chain fatty acid (SCFA) levels in colorectal cancer (CRC) mice. 65 SCFAs are the main end products produced by the fermentation of dietary fiber in the intestines by the intestinal flora. 66 The increase of total fecal SCFA concentration represents the increase of dietary polysaccharide decomposition by bacteria in the gut, which will promote the absorption of polysaccharide energy in the body and play a role in preventing colon cancer.…”
Section: ■ Polysaccharides and Cancersmentioning
confidence: 99%